2003
DOI: 10.1086/379346
|View full text |Cite
|
Sign up to set email alerts
|

The Mass Ratio Distribution in Main‐Sequence Spectroscopic Binaries Measured by Infrared Spectroscopy

Abstract: We report infrared spectroscopic observations of a large well-defined sample of main-sequence, singlelined spectroscopic binaries to detect the secondaries and derive the mass ratio distribution of short-period binaries. The sample consists of 51 Galactic disk spectroscopic binaries found in the Carney and Latham high proper motion survey, with primary masses in the range 0.6-0.85 M . Our infrared observations detect the secondaries in 32 systems, two of which have mass ratios, q ¼ M 2 =M 1 , as low as $0.20. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
100
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(111 citation statements)
references
References 29 publications
8
100
3
Order By: Relevance
“…The narrow peak at q = 1 is reduced as compared with Söderhjelm (2000), because it is not seen by e.g. Mazeh et al (2003), or as a much broader feature by Halbwachs et al (2003). Its total contribution to the above f (q) is only about 6%, and it is relatively unimportant in the present study.…”
Section: Population Synthesis For Binariesmentioning
confidence: 49%
“…The narrow peak at q = 1 is reduced as compared with Söderhjelm (2000), because it is not seen by e.g. Mazeh et al (2003), or as a much broader feature by Halbwachs et al (2003). Its total contribution to the above f (q) is only about 6%, and it is relatively unimportant in the present study.…”
Section: Population Synthesis For Binariesmentioning
confidence: 49%
“…The brightest one is, in its turn, a double-lined spectroscopic binary discovered by Latham et al (1988) and confirmed by Goldberg et al (2002); the low-mass spectroscopic companion is labelled "E". Mazeh et al (2003) Carney et al (1994), which is inconsistent with the F8V spectral type and several effective temperature determinations of components A and E (e.g. Goldberg et al 2002).…”
Section: Wds 20599+4016 (Hd 200077 Ae-d and G 210-44 Ab)mentioning
confidence: 62%
“…Their MRD also depends on the orbital period, since short period binaries (P < 50 days) include more systems with mass ratios of 0.8 or more. Mazeh et al (2003) reported infrared spectroscopic observations of a large well-defined sample of main-sequence, singlelined spectroscopic binaries to detect the secondaries and derive the mass ratio distribution of short-period binaries. Their sample consists of 51 Galactic disc spectroscopic binaries, with primary masses in the range 0.6-0.85 M .…”
Section: The Mrd Of Am Starsmentioning
confidence: 99%